Development of a Self-Contained Power Management System - R., Jeyagopi; Chan, C.K.; M.I.N, Ma'arof (INTI International University, 2022)
The power management system has become an important issue to industries and consumers with the growth of electrical and electronic modern equipment such as house appliances. Power sources increased tremendously with the recently fast-growing population, elevated energy demand volume, and depletion of fossil fuels are aimed at finding an alternative source of energy in the power industry. An abundant source of renewable energy such as solar energy has been shown to be a better choice to satisfy this challenge. Thus, solar energy applications should be advanced using solar panels in this research. The power management system is implemented using solar energy, charging circuit, Lead-Acid battery, and Lithium-Manganese Dioxide battery. This power management system has been developed with the interaction of charging circuits from solar panels to batteries. In this paper, the design was carried out on the solar cells testing with different temperatures to accustom the product. This process is to find the maximum output which the solar panels can deliver. It also includes the part of the battery charging circuit that utilizes the time for charging and recharging the battery. The proposed design is compared with the power system in terms of charging time and reliability of the power source. The results show that the proposed design power management system is able to provide a highly reliable source of power.